"You close the door, wipe your sadness and put on a smiling face": a qualitative study of the emotional labour of healthcare professionals providing palliative care in nursing homes in France - Benoite Umubyeyi; Danièle Leboul; Emmanuel Bagaragaza (BMC, 2024)
Abstract Background Palliative care provided to frail and dying older persons in nursing homes results in intense emotions for residents and their relatives as well as for healthcare professionals. In France, scant attention has been given to how nursing home professionals manage their emotions when providing palliative care. This study analysed the emotional demands of providing palliative care in the nursing home context, the emotional strategies used by healthcare professionals to navigate such demands, and how these demands affect their emotional wellbeing. Methods This qualitative study used a multiple case study approach. We purposively selected nine nursing homes from three geographical provinces in France with diverse ownership statuses (public, private, associative). Individual interviews and focus group discussions were held with 93 healthcare professionals from various occupational groups employed in the participating nursing homes. Data was collected from April 2021 to September 2022 and was analysed using thematic content analysis. Results Data revealed that providing palliative care to dying residents within the nursing home context results in intertwined rewarding and exhausting emotional experiences for healthcare professionals. Professionals have to utilize multifaceted emotional strategies to navigate these experiences, including suppressing and modifying emotions and distancing themselves emotionally from residents to protect themselves from emotional suffering. Participants noted a lack of formal space to express emotions. Unrecognized emotional labour undermines the wellbeing of healthcare professionals in nursing homes, whereas acknowledging emotions enhances satisfaction and gives enhanced meaning to their crucial role in resident care. Conclusion Acknowledging emotional labour as an inevitable component of providing palliative care in nursing homes is critical to supporting healthcare professional wellbeing, resilience, and retention, which may ultimately improve the quality of care for dying residents. Ensuring quality care and supporting the emotional wellbeing of nursing home professionals requires an organisational culture that considers emotional expression a collective strength-building resource rather than an individual responsibility, in hopes of shaping a new culture that fully acknowledges their humanity alongside their professional skills. Trial registration ClinicalTrials.gov ID: NCT04708002; National registration: ID-RCB number: 2020-A01832-37, Registration date: 2020-12-03.